WISP2/IGF1 promotes the survival of DSCs and impairs the cytotoxicity of decidual NK cells. Issue 4 (April 2021) - Shi, Jia-Wei; Yang, Hui-Li; Lai, Zhen-Zhen; Shen, Hui-Hui; Qin, Xue-Yun; Qiu, Xue-Min; Wang, Yan; Wu, Jiang-Nan; Li, Ming-Qing
Abstract : The survival and development of a semi-allogeneic fetus during pregnancy require the involvement of decidual stromal cells (DSCs), a series of cytokines and immune cells. Insulin-like growth factor 1 (IGF1) is a low molecular weight peptide hormone with similar metabolic activity and structural characteristics of proinsulin, which exerts its biological effects by binding with its receptor. Emerging evidence has shown that IGF1 is expressed at the maternal–fetal interface, but its special role in establishment and maintenance of pregnancy is largely unknown. Here, we found that the expression of IGF1 in the decidua was significantly higher than that in the endometrium. Additionally, decidua from women with normal pregnancy had high levels of IGF1 compared with that from women with unexplained recurrent spontaneous miscarriage. Estrogen and progesterone led to the increase of IGF1 in DSCs through upregulating the expression of WISP2. Recombinant IGF1 or DSCs-derived IGF1 increased the survival, reduced the apoptosis of DSCs, and downregulated the cytotoxicity of decidual NK cells (dNK) through interaction with IGF1R. These data suggest that estrogen and progesterone stimulate the growth of DSCs and impair the cytotoxicity of dNK possibly by the WISP2/IGF1 signaling pathway.